Men and women at work in Canada, 1991–2016. (1st October 2020) - Quinn, Emma K.; Harper, Andrew; Rydz, Ela; Smith, Peter M; Koehoorn, Mieke W; Peters, Cheryl E.
ABSTRACT: Women's increased labour force participation in Canada is a well-known trend over the past 40 years, and there is a perception that the gendered division of workplaces has decreased over time. This study aimed to describe the distribution of labour by sex/gender across occupations in the Canadian workforce and to examine changes in this distribution since 1991. We also provide key avenues of inquiry for future research into why occupations are segregated and what we can do about it. Data were obtained from the last six Canadian Censuses of Population (1991–2016). Descriptive statistics were prepared to examine labour force composition within various resolutions of the National Occupational Classification (NOC) codes by sex. GEE Poisson regression models were used to generate time- and occupation-adjusted estimates for incidence rate ratios with corresponding 95% confidence intervals for sex/gender differences in worker population growth. Over 40% of broad occupational categories were highly divided; three-quarters were mainly composed of men. For the most precise classifications, 58% of occupations were highly divided (78% mainly composed of men). Our inquiry into the forces driving sex-segregated jobs found that systems of gender essentialism, organisational hierarchies that favour men, and labour markets that are change-resistant are our future challenges. Abbreviations NOC: National Occupational Classification; NOC-S: National Occupational Classification for Statistics; ATV: all-terrain vehicle; GEE: generalised estimating equation; IRR: incidence rate ratio; CI: confidence interval; STEM: science, technology, engineering, and mathematics